Impact of Climate-Smart Agricultural Cooperatives on Conflict Prevention and Rural Prosperity in West Africa - Bello, Mukhtar (Kashere Journal of Politics and International Relations, 2025)
The climate change exacerbates resource conflicts and undermines rural livelihoods in West Africa, yet climate-smart agricultural (CSA) cooperatives offer a promising solution. This study investigates how CSA cooperatives in Ghana and Senegal reduce land and water conflicts while enhancing rural prosperity. Using a mixed-methods case study approach, data were collected from local government records, NGO reports, and focus group discussions with cooperative members. In Ghana’s Asunafo North Cooperative, agroforestry and land-use agreements increased maize yields by 39% and incomes by 28%, while reducing farmer-herder disputes by 70% between 2018 and 2024. In Senegal’s Louga Water Users’ Cooperative, drip irrigation and water-sharing agreements boosted rice yields by 28% and incomes by 32%, cutting water-related conflicts by 80%. Community perceptions highlight cooperatives as platforms for trust and economic stability, reinforcing peace. Challenges include funding constraints, limited technology access, and policy gaps. The findings address a gap in understanding CSA cooperatives as dual drivers of peacebuilding and economic resilience, offering a scalable model for climate-vulnerable regions. Recommendations include sustained funding, stronger policy integration, and inclusive governance to scale cooperative impacts. This study underscores the potential of CSA cooperatives to transform resource scarcity into opportunities for collaboration and prosperity in West Africa.